A Description of Mental Health Policies in Ohio Secondary Schools - Laura Harris; Molly Rowe (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
OBJECTIVE To compare secondary school mental health policies implemented for the student body with those implemented for student athletes.